2013
DOI: 10.1002/cbm.1851
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of male 14‐ to 20‐year‐olds on probation and in a residential home in Hong Kong

Abstract: Participants in this study generally reported higher levels of positive psychological well-being than in previous nondelinquent Chinese samples. IMPLICATIONS FOR PRACTICE AND FUTURE RESEARCH: A case-control study comparing such offenders with nondelinquents is required to clarify these findings. A longitudinal design is now indicated to test the direction of relationships between psychological indicators and offending. These steps would be useful precursors to a service evaluation of probation hostels for youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although in previous works (e.g. Chui & Chan, 2012b, 2013 there have been some support of the correlations between pro-offending attitudes and criminal behaviour among young offenders in Hong Kong, this study extends the literature by utilising an established measure of criminal attitudes, the CSS-M, and testing the relationship between criminal sentiments and law violations of young people in Hong Kong. This study also took into consideration measures of social factors of youth that have been found to influence delinquent behaviour in the Hong Kong context (e.g.…”
Section: Criminal Attitudes and Behaviourmentioning
confidence: 85%
“…Although in previous works (e.g. Chui & Chan, 2012b, 2013 there have been some support of the correlations between pro-offending attitudes and criminal behaviour among young offenders in Hong Kong, this study extends the literature by utilising an established measure of criminal attitudes, the CSS-M, and testing the relationship between criminal sentiments and law violations of young people in Hong Kong. This study also took into consideration measures of social factors of youth that have been found to influence delinquent behaviour in the Hong Kong context (e.g.…”
Section: Criminal Attitudes and Behaviourmentioning
confidence: 85%
“…In this study we have linked the female role to women and the male role to men and have found differences. These can be related to aspects that each stereotyped gender marks as its own, differentiating between male and female to achieve life satisfaction (Chui et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Rosenberg Self-Esteem Scale was used to measure participants' selfvalue and self-acceptance (Rosenberg, 1965). The scale has been found to work well with Hong Kong Chinese samples, with internal consistency estimates ranging from 0.67 to 0.88 (see, e.g., Cheuk, Wong, & Rosen, 2011;Chui & Chan, 2013;Tse, Wu, & Poon, 2011). The scale has 10 questions in a 4-point response format.…”
Section: Self-esteemmentioning
confidence: 99%